Letter from the Jewish Welfare and Youth Office to Max Bredig (1934)
The Jewish Welfare and Youth Office in Berlin thanks Max Bredig (1902-1977) for his recent monetary donation.
Keywords: Bredig, Max Albert, 1902-1977